Manajemen Sistem Informasi Akuntansi Penjualan Menggunakan Microsoft Visual Studio 2019 di Café More Wyata Guna Bandung - Gilang Nur Akbar; Gilang Ramadhan; Muthmainnah; Seliwati (KITA Institute, 2022)
Café more is a business project of the Indonesian Ministry of Social Affairs through the Center for Social Rehabilitation of Persons with Sensory Disabilities Netra Wyata Guna Bandung. The author's purpose of conducting this research is to compile a management design for sales accounting information system using Microsoft Visual Studio 2019 and database MySQL. In this study, the authors use qualitative methods with interview data collection methods, literature study data or observation. And also the system development method used is the prototype. From the results of this study, a problem was found, namely the processing of cafe more sales data reports is still manual so that sales reports are still irregular and prone to errors in making the report and the information presented is less accurate. With this sales information system management design, the author hopes to simplify the work of employees in managing sales data and sales reports quickly and accurately.